ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN TERHADAP SAP OLEH PEMERINTAH DAERAH - Lambok Maranatal; Dwi Ratmono (Diponegoro Journal of Accounting, 2017)
This study aimed to analyze the factors that influence compliance with Government Accounting Standards (GAS) by the local government. The independent variables were tested in this study is the size of the local government, the ratio of financial conditions, transfer ratio, population, employees and the audit findings of non-compliance to compliance with Government Accounting Standards (GAS). The dependent variable was tested using an index of compliance.This study uses secondary data derived from the results of the examination report the Audit Board on the Local government Financial Report in Central Java periods in 2014 and 2015. The research sample as many as 34 LGFR in Central Java each year. The total sample is 68 LGFR of 2 years of observation. The analytical method used is multiple linear regression analysis.The results showed that the audit findings of non-compliance, financial conditions and transfer ratio have significantly negative effect on compliance with Government Accounting Standards. The size of the local government, population and employees do not have a significant influence on compliance with Government Accounting Standards.